Mobs who Stripped Female Robbers but Failed to Strip the Male Robbers: The “Evil Women Hypothesis” on Nigerian Streets - Agazue, Chima (International Journal of Criminology and Sociology, 2023)
Academic reports on the “evil women” hypothesis have focused mainly on the actions of criminal justice authorities (CJA). However, actions based on this hypothesis equally extend to ordinary members of the public. Vigilante justice on suspected criminals by mobs is a regular occurrence in Nigeria. Thus, the current article drew on vigilante justice on robbers to examine the notion of the evil women hypothesis from the perspective of mobs. Three robbery incidents in three different Nigerian cities involving robbers impersonating taxi operators known as “one-chance” robbers, were analyzed. In all the three incidents, the one-chance robbers comprising both men and women were caught by mobs. In all of them, the mobs stripped the female robbers naked in public whilst their male gang members were allowed to wear their clothes. The actions of the mob conformed to those of CJA with respect to the evil women hypothesis whereby female offenders are punished more severely than their male counterparts due to the idea that the former have crossed the morality boundary to commit a serious offense that goes against the gender-role expectations.